Development of the system diagnostic damping characteristic of the rolling stock dampers - Єременко, Володимир Станіславович; Шегедін, Петро Анатолійович; Переїденко, Антон Володимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper describes developed by authors information-measuring system of diagnosing damping characteristics of rolling stock dampers. The system includes the hardware for gathering and digital processing of vibration accelerations and software for accelerometer sensor signal processing. It suggests testing procedure to determine the damping characteristics and algorithms to calculate damping parameters, namely the logarithmic decrement and natural oscillation frequency of the structure. It proposes to use an alternative error-correcting method, which lies in calculating the logarithmic decrement in the frequency domain. The advantage of this method is the high determination accuracy of damping parameters and the absence of high-frequency noise effect on the calculation result since the frequency and quality factor determination proceeds in the low frequency signal range and noise is of high-frequency nature. The paper also proposes software, developed in the LabVIEW graphical programming environment that implements the standard and the suggested algorithms and presents the comparative analysis of the experimental data processing results. It also shows the results of system approbation during testing the locomotive CHS-8 and passenger cars.